2017
DOI: 10.1111/ijmr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Small Business Social Responsibility: A Critical Multilevel Review, Synthesis and Research Agenda

Abstract: Small business social responsibility (SBSR) related research is rapidly increasing in quantity but is found in divergent literatures and disciplines. It is time to offer a comprehensive review that identifies, synthesises, and integrates previous research, and highlights the knowledge gaps and the way forward. Our methodical search of the literature helped identify 115 multidisciplinary peer-reviewed academic articles appearing in high quality journals over the 1970-2016 period. Using a systematic and in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 146 publications
(153 reference statements)
2
105
0
1
Order By: Relevance
“…As a recommendation we point out that companies should consider developing CSR strategies and promoting its implementation with the support of their chief officer of CSR or CSO once the importance of their functions is recognized beyond the tools presented previously based on literature, once it is considered that in CSR terms respond to social, and environmental issues are needed in developing and emerging economies (Soundararajan, Jamali, & Spence, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a recommendation we point out that companies should consider developing CSR strategies and promoting its implementation with the support of their chief officer of CSR or CSO once the importance of their functions is recognized beyond the tools presented previously based on literature, once it is considered that in CSR terms respond to social, and environmental issues are needed in developing and emerging economies (Soundararajan, Jamali, & Spence, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies differentiate between socially responsible activities engaged in by SME owners and CSR activities, previously perceived to be poorly translated in the SME context (Soundararajan et al, 2018). This study focuses on the latter, as integrating CSR (i.e., introducing codes of conduct, standards, reporting) is perceived to be problematic (Baden et al, 2011).…”
Section: The Unique Context Of Family Smes and Social Responsibility mentioning
confidence: 99%
“…There is a growing interest in knowing how deep socially responsible activities run in smalland medium-sized family businesses (Baden, Harwood and Woodward, 2011;Soundararajan, Jamali and Spence, 2018). Family SMEs represent the largest share of businesses worldwide (Howorth, Rose, Hamilton and Westhead, 2010) and their socially responsible engagement, progressively reported under a corporate social responsibility (CSR) label, has not gone unnoticed (Van Gils, Dibrell, Neubaum and Craig, 2014;Spence, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Again, although we acknowledge that explicit and implicit CSR communication co-exist in large as well as in small and medium firms, prior research has pointed to how explicit communication has primarily been salient in large firms and implicit communication been salient in small and-medium sized enterprises. A review of research has indicated how this balance is currently changing for SMEs (Soundararajan et al, 2017); our interest is in exploring the implications thereof.…”
mentioning
confidence: 99%